Underlying factors of cost overruns in developing countries: multivariate analysis of Jordanian projects - Faten, Ahmad Albtoush; Doh, Shu Ing; Abdul Rahimi, Abdul Rahman (2020)
While all project parties agree that exceeding the budget results in project failures, most construction projects in Jordan are suffering from cost overruns. Understanding the root cause of the issue is critical to solve the problem comprehensively. However, the previous studies lack information on the underlying causes that are resulting in cost overruns among the nation’s construction projects. The principal purpose of this study is to identify the most significant causes of cost overruns in Jordanian construction projects. Therefore, the researcher used the quantitative approach for data collection through questionnaire survey among stakeholders in the construction project. This study uses the principles of multivariate statistics in analyzing the causes of cost overruns in Jordanian construction projects. The findings revealed that the four major underlying causes for cost overruns in Jordan are financial difficulties, materials issues, design issues and additional works. Besides, the results also revealed that high transportation cost, unrealistic contract duration, slow decision making, extra quantity during construction, inadequate funds for project financing, inconsistent cash flows and payment problems faced by the clients from the government are critical sub cause for cost overruns in the region. The findings on the critical and underlying causes for cost overruns may help industrial practitioners in developing strategies to achieve better project success.